PEMBIMBINGAN KEPRIBADIAN DAN KEMANDIRIAN KLIEN PEMASYARAKATAN UNTUK MEWUJUDKAN REINTEGRASI SOSIAL (Studi Pada Balai Pemasyarakatan Kelas I Padang) - Purwaningrum Purwaningrum (UNES Law Review, 2022)
The role of the Correctional Center in particular is to provide guidance to Correctional clients as regulated in Government Regulation Number 31 of 1999 concerning Guidance and Guidance of Correctional Inmates. To realize Social Integration, it is necessary to provide personality and independence guidance to correctional clients. The personality and independence guidance program carried out by the Padang Class I Penitentiary has so far not been running as it should. For this reason, efforts to improve the program are needed in accordance with statutory regulations.